Evaluating seroprevalence to circumsporozoite protein to estimate exposure to three species of Plasmodium in the Brazilian Amazon - Virginia Araujo Pereira; Juan Camilo Sánchez-Arcila; Mariana Pinheiro Alves Vasconcelos; Amanda Ribeiro Ferreira; Lorene de Souza Videira; Antonio Teva; Daiana Perce-; Maria Teresa Queiroz Marques; Luzia Helena de Carvalho; Dalma Maria Banic; Luiz Cristóvão Sobrino Pôrto; Joseli Oliveira-Ferreira (BMC, 2018)
Abstract Background Brazil has seen a great decline in malaria and the country is moving towards elimination. However, for eventual elimination, the control program needs efficient tools in order to monitor malaria exposure and transmission. In this study, we aimed to evaluate whether seroprevalence to the circumsporozoite protein (CSP) is a good tool for monitoring the exposure to and/or evaluating the burden and distribution of Plasmodium species in the Brazilian Amazon. Methods Cross-sectional surveys were conducted in a rural area of Porto Velho, Rondônia state. Parasite infection was detected by microscopy and polymerase chain reaction. Antibodies to the sporozoite CSP repeats of Plasmodium vivax, P. falciparum, and P. malariae (PvCS, PfCS, and PmCS) were detected using the enzyme-linked immunosorbent assay technique. Human leukocyte antigen (HLA)-DRB1 and DQB1 genes were typed using Luminex® xMAP® technology. Results The prevalence of immunoglobulin G against P. vivax CSP peptide (62%) was higher than P. falciparum (49%) and P. malariae (46%) CSP peptide. Most of the studied individuals had antibodies to at least one of the three peptides (72%), 34% had antibodies to all three peptides and 28% were non-responders. Although the majority of the population was not infected at the time of the survey, 74.3% of parasite-negative individuals had antibodies to at least one of the CSPs. Importantly, among individuals carrying the haplotypes DRB1*04~DQB1*03, there was a significantly higher frequency of PfCS responders, and DRB1*16~DQB1*03 haplotype for PvCS and PfCS responders. In contrast, HLA-DRB1*01 and HLA-DQB1*05 allelic groups were associated with a lack of antibodies to P. vivax and P. falciparum CSP repeats, and the haplotype DRB1*01~DQB1*05 was also associated with non-responders, including non-responders to P. malariae. Conclusions Our results show that in low transmission settings, naturally acquired antibody responses against the CSP repeats of P. vivax, P. falciparum, and P. malariae in a single cross-sectional study may not represent a valuable marker for monitoring recent malaria exposure, especially in an area with a high prevalence of P. vivax. Furthermore, HLA class II molecules play an important role in antibody response and require further study with a larger sample size. It will be of interest to consider HLA analysis when using serosurveillance to monitor malaria exposure among genetically diverse populations.